Islamic Clothing and the Modern Woman (Intellectual Study) (Journal of the College of Education for Women, 2019)
In the name of Allah, the Beneficent, the Merciful.Praise be to Allah, Lord of the Worlds and peace and blessings on the honest and trustworthy (Muhammad) and his family and his divine good companions.The Islamic clothing is one of the requirements of the common and original innateness to humans; the innateness that is created by God to all people, Allah says, (So set thou thy face steadily and truly to the Faith: [establish] Allah's handiwork according to the pattern on which He has made mankind: no change [let there be] in the work [wrought] by Allah: that is the standard Religion: but most among mankind understand not) (1). Islam as a natural religion has ordered the Muslims to wear decently, Allah says, ( O Children of Adam! wear your beautiful apparel at every time and place of prayer: eat and drink: But waste not by excess, for Allah loveth not the wasters.) (2). This Verse is addressed for men and women; it indicates the meaning of (adornment) as a dressed decently at every place of warship such as (Mosque, Cruising around the Kaaba, and Prayer). The Islamic clothing is the basic principle that is intended to maintain a society of decay and corruption. I chose this topic to be tackled in my research for its highly importance within the people's concerns at the moment. May God help me to clarify this subject completely tackling the Islamic clothing, adornment damaging to society, and the conclusion includes some suspicions with their answers.The research includes three sections:- The First Section: The Islamic clothing in the Islam:- The first objective: The Islamic clothing as a language and an idiom.- The second objective: Rule and the conditions of the Islamic clothing in Islam.The third objective: The wisdom of the legitimacy of the veil ( hijab ) in Islam.- The Second Section: Adornment and its aspects, reasons, and damages.- The first objective: Adornment appearances.- The second objective: Adornment reasons.- The third objective: Adornment damages.- The Third Section: Suspicions relating to the veil ( hijab ).The conclusion of this research includes the following results:1- The Islamic woman is not enjoined and imposed what she can't afford to do; the Islam sets some rules and conditions that allowed her to follow them easily, and gives her the right to select her dress and the permitted colors that fit her personality without any difficult constraint.2- The veil ( hijab ) is a comprehensive program for the Muslim woman's life; it is not just used to cover her body but it governs the rest of her actions.3- The postulate of the veil ( hijab ) came to realize the greatest purpose of the Islamic law which is the honor protection, and maintain a community of degeneration. The fixed statistics of the obscenity and crimes in the western world improve this presupposition.The veil ( hijab ) is a means by which a woman expressed her own freedom and not the opposite as some people claim. The Islamic clothing with its rules and conditions represents the top of the advancement and evolution and not a tardiness as the objectors say. It is better suited with the right innateness of Man that is created by God; and it is the essential reason ofdeveloping the communities, their construction, and progress as well as maintaining them of the deviation and sin.